Inclusion strategy for mobile technology in the classroom: experience at the Universidad de Tarapacá - Bustos Andreu,Hernando (Universidad de Tarapacá., 2011)
Despite the existence of recognized benefits of the use of information and communication technology in education, the employment of such technology is a complex process that needs appropriate planning and structuring to obtain good results. This article shows the results obtained from the application of a consistent strategy to a set of action plans oriented to the incorporation of a mobile technology platform in the classroom. The results obtained in this experience at the Universidad de Tarapacá allowed us to establish that the process was successful with regard to the academic aspect and detect new imperatives for the inclusion process.